2012
DOI: 10.1021/ma202267r
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dielectric Hysteresis in Multilayered Films via Nanoconfinement

Abstract: Micro/nanolayer coextrusion was used to fabricate polycarbonate (PC)/poly(vinylidene fluoride) (PVDF) layered films with significantly reduced dielectric losses while maintaining high energy density. The high-field polarization hysteresis was characterized for layered films as a function of PVDF layer thickness (6000 to 10 nm) and composition (10 to 70 vol % PVDF), and was found to decrease with decreasing layer thickness and PVDF content. To gain a mechanistic understanding of the layer thickness (or nanoconf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(205 citation statements)
references
References 51 publications
4
196
4
Order By: Relevance
“…Al electrodes appeared to be more resistant to the electrochemical reaction than Ag electrodes. To prevent direct electrochemical reactions between PVDF and the metal electrodes, we propose to carry out future research to sandwich PVDF with thin layers of a stable dielectric polymer such as PC (e.g., in multilayer films 13,56 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al electrodes appeared to be more resistant to the electrochemical reaction than Ag electrodes. To prevent direct electrochemical reactions between PVDF and the metal electrodes, we propose to carry out future research to sandwich PVDF with thin layers of a stable dielectric polymer such as PC (e.g., in multilayer films 13,56 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Discussionmentioning
confidence: 99%
“…Considering Au is too expensive to be used as metal electrodes for practical applications, we propose to end-cap PVDF with a dielectric polymer (e.g., polycarbonate, PC) in a sandwich geometry or in multilayer films 13,56 to prevent direct contact of PVDF with metal electrodes. This research currently is under investigation and will be reported in the future.…”
Section: °mentioning
confidence: 99%
“…Both mechanisms can be realized if the film contains a very large number of individual layers (and hence many interfaces). Recently, Baer and colleagues (35,36) demonstrated nanomultilayers consisting of alternating PC and PVDF (or PVDF-based copolymer) layers. PC is a low-permittivity (K = 3), low-loss polymer, whereas PVDF-based polymers have higher permittivity (K = 10-15) and higher loss.…”
Section: Improvements In the Performance Of Pvdf-based Copolymers Andmentioning
confidence: 99%
“…Moreover, by combining VDF-based ferroelectric polymers (high polarization and large hysteresis loss) and low-K, low-loss materials with the nanoconfinement effect offered by the large number of interfaces, this approach also leads to a significant reduction in energy loss. For instance, the loss in a PC-PVDF multilayer with <100-nm individual layers and 30-70% volume fraction of PC can be reduced by nearly one order of magnitude compared with the loss in pure PVDF (35). A similar multilayer approach has been adopted in other polymer-inorganic (41) and self-assembled all-organic (42) systems.…”
Section: Improvements In the Performance Of Pvdf-based Copolymers Andmentioning
confidence: 99%
“…5(c)), reducing the generation of charge carriers which may results in ionic or dc conduction and decreases electric breakdown strength, via decreasing the concentration of ionizable hydroxyl groups and ion migration on the surface of BT nanoparticles. 31,32 Furthermore, due to the well dispersion of surface modified BT nanoparticles, more interfaces play as active roles to the enhanced electric breakdown properties (Fig. 5(d)), having positive influences on interfacial charge around the surface of BT nanoparticles and charge concentration associated with the diffuse double layers between BT nanoparticles and PVDF matrix.…”
Section: Electric Breakdown Strength and Energy Densitymentioning
confidence: 99%